Effective Piezo‐Phototronic Enhancement of Flexible Photodetectors Based on 2D Hybrid Perovskite Ferroelectric Single‐Crystalline Thin‐Films (Adv. Mater. 32/2021). Issue 32 (12th August 2021) - Ding, Ran; Lyu, Yongxin; Wu, Zehan; Guo, Feng; Io, Weng Fu; Pang, Sin‐Yi; Zhao, Yuqian; Mao, Jianfeng; Wong, Man‐Chung; Hao, Jianhua
Abstract : Photodetectors In article number 2101263, Jianhua Hao and co‐workers report the use of ferroelectric EA4 Pb3 Br10 single‐crystalline thin‐films to broaden perovskite photodetection applications with piezo‐phototronic effect enhanced behavior. The coupling of ferroelectric spontaneous polarization and the piezoelectric effect, as well as photoexcitation and semiconductor behaviors endow the EA4 Pb3 Br10 ‐based flexible photodetectors with a strain‐modulated capability, giving rise to an effective enhancement of photodetection performance via the piezo‐phototronic effect.